Representations of Pan-Africanism in the contemporary post-Apartheid South African high school history classroom - Karadag, Esma (African Studies, 2025)
This is an interdisciplinary study on the representation of Pan-Africanism in history classrooms in high schools in contemporary post-apartheid South Africa. The subject History is part of the curriculum's stated vision to mould learners' identities in relation to key national and continental post-colonial foundations, such as Pan-Africanism (Department of Basic Education [DBE], 2011). Employing a qualitative empirical method, the study aims to gain insight into the contemporary responses to Pan-Africanism in South African high school history classrooms through the perspectives of teachers. How do they represent the concept in history classrooms, engage textbooks and students on the concept, and what do they report on the contemporary views of their history students on Pan-Africanism? Using reflexive thematic analysis, the study highlights significant and bifurcated variations that exist in the representation of Pan-Africanism through the perspectives of teachers across classrooms, intricately linked to social class. This key finding confirms Stuart Hall's (1997) cultural theory on representation, which emphasises the role of cultural and historical contexts in which meaning is ‘fixed' through the systemisation process of ‘encoding' and ‘decoding', thereby reinforcing or challenging existing power structures. The study illustrates the teachers' agencies in constructing varied representations of Pan-Africanism in the contemporary history classroom situated in contrasting post-apartheid socio-economic contexts, in which new shared and contested cultural codes and conceptual meanings are created.